Bridging the Gap in Girls’ Education through Open Schooling in India Prospects and Provisions - Kaushal, Savita (JOURNAL OF INDIAN EDUCATION, 2012)
Education of girls has been a high-priority area for the Government of India. The Central and State Governments have been making efforts to achieve the goal of Universalisation of Elementary Education. Despite the initiatives, the gender gap in India has persisted in the field of education since Independence. Enrolment of boys is more than girls at all levels of school education and dropouts rates for girls are also higher – indicative of a gender gap that needs to be bridged (though in recent years, it has narrowed considerably at the elementary stage). Though the situation continues to improve, girls still have lower enrolments, lower attendance rates as well as higher drop out rates compared to boys. Open schooling has created enormous opportunities for the expansion of educational opportunities. A variety of variables pertaining to open schooling appear to have made an impact on learners’ response to open schooling – the structuring of the programme and its requirements, the in-built flexibilities created for the learners – all independently and collectively influence the enrolment of both male and female learners in open schooling. With this context, the present paper seeks to uncover the impact of different aspects of open schooling in enrolment and retention of the female learners.